La gouvernance des espaces publics à l’épreuve de l’informalité. Conflits, corruption et pratiques du droit dans l’occupation des rues par les vendeurs informels à Mumbai - Lola Salès (L'Espace Politique)
Since the economic reforms of the 1990’s, street vending plays an important part in everyday life and urban economy in many cities all over India. In Mumbai, street trading allows a large part of urban dwellers to earn a living and provide some essential and affordable goods to the population. However, this activity seems to be “unwanted”, according to urban planning and governance policies and according to a part of “civil society” discourses. Consequently, street vendors are central in the conflicts about public space, which represent a working and living place, a vital spatial resource but also a place for fluent traffic, leisure activities, flânerie or consumption. Moreover, for a large part of official and non-official urban actors, public spaces are a source of informal income through corruption and clientelism practices. Indeed, hawkers, considered as illegal, are victims of a huge extortion process by the municipality and police but also by some informal actors. A new law for the defence of street vendors’ rights (Street vendors Act) has been voted in March 2014 at central level, and recognizes the legitimacy and the legality of these activities through a regularization process. In this context, this article tries to analyse the use of law in public spaces conflicts, as well as concrete practices of law through transgressions and negotiations. Analysing informality seems to be a relevant case to understand the tensions between the normative aspect of public spaces and the diversity of their modalities of appropriation, and the plurality of powers which are ruling public spaces occupation.